Lifting Moving Management with Role Play Method On Volunteers Mojokerto Tanggap Bencana (MTB) - Heni Fauziah; Agus Haryanto; Eka Nur So’emah; Mufarika Mufarika (International Journal of Nursing and Midwifery Science (IJNMS), 2025)
Lifting and moving disaster victim management skills  are important competencies for volunteers. Incorrect techniques can aggravate the victim's injury, but it is also at high risk of causing back injury to volunteers. Mojokerto Tanggap Bencana (MTB) volunteers need effective training methods to ensure safe mastery of techniques. The Role Play method was chosen because it offers a simulation of real situations of hands-on practical learning. analyzes the effect of the application of the Role Play method  on the improvement of the knowledge and skills of lifting moving victims in MTB volunteers. This study used a quasi-experimental design of One-Group Pretest-Posttest with a total sampling technique of 56 active MTB volunteers. The intervention provided was lifting moving training using the Role Play method. Knowledge was measured using  an intervention pre-post test questionnaire  . Skills were measured using  a standard checklist on a score scale of 0-100. Data analysis was carried out by paired t-test. The implementation of lifting moving management by volunteers prior to role play training  is still low, with nearly half of respondents (48%) rated "Not Appropriate." However, role play training succeeded in substantially improving the competence of volunteers, as shown by a significant surge in respondents who carried out according to the SOP to (86%). The results of paired t-test confirmed that there was a significant influence of the method with a p value of 0.000<α(0.05), this proves the effectiveness of the role play method  in improving lifting moving management. Simulations that are close to field conditions, coupled with live feedback, allow volunteers to internalize  safe lifting moving techniques  and practice decision-making skills. The Role Play method  is effective in increasing the knowledge and management skills  of  lifting moving victims in MTB volunteers.